Following in Banting’s footsteps or straying from the path? Observations from contemporary diabetes innovation - Leadley, Connor; Addala, Ananta; Berkeley, Juliet; Crocket, Hamish; Davis, Elizabeth A.; Hewapathirana, Niranjala; Hussain, Sufyan; Lal, Rayhan; Lomax, Kate; Wilkinson, Thomas; de Bock, Martin; Burckhardt, Marie-Anne (Frontiers in Endocrinology, 2023)
While advancements in the treatment of diabetes continue to rapidly evolve, many of the newer technologies have financial barriers to care, opposing the egalitarian ethos of Banting who sold his patent on insulin for a nominal cost to allow it to be made widely available. Inequity in access to new therapies drives disparity in diabetes burden with potential for these gaps to widen in the future. The 2023 International Conference on Advanced Technologies and Treatments of Diabetes (ATTD) presented ground-breaking and current research in diabetes technology. Oral presentations of the ATTD conference 2023 were analyzed to describe what percentage of speakers discussed equity in their talks. Overall, less than a quarter of presenters discussed equity, though there was regional variation. To ensure that diabetes technologies reduce disparity and improve outcomes, we encourage future speakers at diabetes (technology) conferences to consider equity of diabetes care and incorporate this into their presentations.